International Firm Activities and Innovation: Evidence from Knowledge Production Functions for German Firms - Joachim Wagner (Max Planck Institute of Economics, 2006)
Using a knowledge production framework and a rich set of plant level data this study demonstrates that in Germany firms that are active on international markets as exporters or foreign direct investors do generate more new knowledge than firms which sell on the national market only. These differences are not only due to a larger firm size, or different industries, or the use of more researchers in these firms, but due to the fact these globally engaged firms learn more from external sources, too. The importance of these knowledge sources varies with the type of innovation. These results, which are broadly in line with the findings of a recent study using UK firm level data, can help to explain the strong positive correlation between productivity and international activities of firms. Firms that are active on markets beyond the national borders generate higher levels of new knowledge that feed into higher productivity.
Keywords: F14; F23; O31; 330; Exports; foreign direct investment; knowledge production function; Germany; Wissen; Produktionsfunktion; Innovation; Exportindustrie; Multinationales Unternehmen; Wissenstransfer; Lernprozess; Schätzung; Deutschland